Struvite as a Sustainable Fertilizer in Mediterranean Soils - Pérez-Piqueres, Ana; Ribó, Marta; Rodríguez-Carretero, Isabel; Quinones, Ana; Canet, Rodolfo (MDPI, 2023)
Recycled sources of phosphorus (P) and nitrogen (N), such as struvite extracted from wastewater, have the potential to substitute conventional manufactured fertilizers and mitigate environmental problems such as water eutrophication or the depletion of non-renewable resources. This study aimed to evaluate the potential of struvite as a nitrogenous and phosphate fertilizer in the Spanish Mediterranean region. Two experiments were carried out using struvite recovered from sewage sludge and different representative soils from the area. Since knowing the rates at which their nutrients are released is key for efficient use, experiment I determined the struvite N-releasing rate for 16 weeks. Experiment II studied the effect of different struvite doses (50, 100, 200 kg P2O5 ha−1) on crop growth compared to superphosphate + ammonium nitrate. The results indicated N-releasing rates that fall in line with a slow-release fertilizer. More than 20% of applied struvite-N was unavailable for plants or in the longer term, which suggests struvite fractionation as the most efficient application method. Struvite showed similar fertilization capacity, which was even better at some points, than conventional mineral fertilization, plus adequate plant growth and good nutrient concentration at the 50 kg P2O5 ha−1 dose. Based on this study, struvite can be considered an interesting and effective option for sustainable fertilization in the Mediterranean region.